2010
DOI: 10.1128/aem.00615-09
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Distribution ofSalmonella entericaSerovar Typhimurium in Loamy and Sandy Soil Monoliths with Applied Liquid Manure

Abstract: A leaching experiment, where liquid manure spiked with Salmonella enterica serovar Typhimurium (Tet ؉ ) DSM554 was applied to soil surfaces, was conducted on intact soil monoliths (60 cm in diameter and 100 cm long). A total of 6.5 ؋ 10 10 CFU was applied to each column. We found that Salmonella serovar Typhimurium could be transported to a 1-m depth in loamy soil at concentrations reaching 1.3 ؋ 10 5 CFU/ml of leachate. The test strain was found in concentrations ranging from 300 to 1.3 5 cells/ml in loamy so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…The bacterial cells cannot be cultured by traditional culture-based methods but only be identified by direct detection, including molecularly based methods (21). VBNC cells introduced to the soil environment did not display enhanced persistence compared to culturable cells (51), and the presence of equal numbers of total and culturable Salmonella cells in the leachate from soil monoliths indicated that most cells leaching were viable (9). Thus, even under fluctuating temperatures and with natural precipitation, viable microbial tracers leached through intact soil cores with a survival/inactivation time similar to or higher than that reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterial cells cannot be cultured by traditional culture-based methods but only be identified by direct detection, including molecularly based methods (21). VBNC cells introduced to the soil environment did not display enhanced persistence compared to culturable cells (51), and the presence of equal numbers of total and culturable Salmonella cells in the leachate from soil monoliths indicated that most cells leaching were viable (9). Thus, even under fluctuating temperatures and with natural precipitation, viable microbial tracers leached through intact soil cores with a survival/inactivation time similar to or higher than that reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Carlander et al (15) observed a rapid transport of Salmonella bacteriophage 28B in clay soils, with breakthrough (i.e., from the time of application to the detection in the leachate) at a depth of 1.2 m after 2 to 24 h, probably due to the presence of macropores and bypass flow. Salmonella enterica serovar Typhimurium was detected in leachate from intact clay monoliths 24 h after manure application (9), and fecal coliforms originating from dairy shed effluent readily penetrated through 700-mm-deep soil columns within 2 days (43). C. parvum oocysts applied to soil blocks that were subsequently irrigated with artificial rainwater on alternate days were transported within a silty loam soil and detected for up to 9 days in leachate, whereas the oocysts added to clay loam soil blocks could be detected over 21 days in the leachate (54).…”
mentioning
confidence: 99%
“…Bacterial transport in runoff from application of various types of manures, including poultry, has been widely studied (Soupir et al, 2006;Jenkins et al, 2008;Brooks et al, 2009;Harmel, 2009;Guzman et al, 2010;Sistani et al, 2010;Delgado et al, 2011). Laboratoryscale studies have shown that SALM and other pathogens can be transported through over 1 m of soil, and transport is controlled by soil types, hydrodynamic forces, physical filtration, and interactions between bacterial surface-charges and air, water, and soil interfaces (Haznedaroglu et al, 2009;Bech et al, 2010;Chen, 2012). Studies show increased bacterial transport under saturated conditions; however, transport has also been shown to occur under unsaturated conditions when preferential flow paths, such as vermicular macropores, are present (Beven and Germann, 1982;Abu-Ashour et al, 1998;McMurry et al, 1998;Bottinelli et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Gannon et al (12) found that cell size was the main factor controlling transport of microorganisms in repacked soil. On the other hand, in structured soil this filtering effect can be severely reduced by preferential flow and macropore flow (13,14), and microorganisms may move with runoff or infiltrating water as free cells and/or attached to soil and manure particles (15,16,17). While the environmental fate of manure-borne contaminants has received attention in the past (5,11), there are recent developments in manure management techniques for improved nutrient use efficiency and odor control, including solid-liquid separation (18,19) and field application methods, that may alter the environmental fate of some contaminants (20,21).…”
mentioning
confidence: 99%